Collaborative Governnace dalam Penyelenggaraan Pendidikan Inklusif Tingkat SMP di Kota Surabaya - Handini Zakiyyah Damayanthi; Roisul Basyar; Hasan Ismail (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
This research examines the collaborative governance process in implementing inclusive education programs at the junior high school (SMP) level in the city of Surabaya. The research background stems from the gap between the increasing number of children with special needs and the limited inclusive education services available, where of the 661 junior high schools in the city of Surabaya, only 66 have inclusive school status. This research aims to analyze the collaborative governance process in implementing inclusive education programs at the junior high school level in the city of Surabaya. Using descriptive qualitative research methods, data was obtained through in-depth interviews, observation, and documentation at the Surabaya City Education Office, SMP Negeri 36 Surabaya, SMP Negeri 55 Surabaya, and SMP Galuh Handayani Surabaya. The research results show that collaborative governance in inclusive education in the city of Surabaya has gone quite well. This is demonstrated by the existence of clear regulations (Perwali No. 52 of 2022), the formation of the Inclusion Working Group and Disability Service Center, facilitative leadership from the Education Office and school principals, as well as a collaborative process involving face-to-face dialogue, building trust, mutual commitment, mutual understanding, and the results of collaboration in the form of increasing access and quality of inclusive education services. However, there are obstacles in the form of limited Special Assistant Teachers (GPK) and the unbalanced expansion of policies with the availability of supporting resources.